2011
DOI: 10.1080/19425120.2011.620908
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Gulf Menhaden Recruitment and Mississippi River Flow: Model Development and Potential Application for Management

Abstract: The Gulf menhaden Brevoortia patronus is one of the most abundant pelagic fishes in the northern coastal Gulf of Mexico (hereafter, "Gulf") and is the principal forage for various commercial and sport fishes, sea birds, and marine mammals. Part of the life history of Gulf menhaden is spent on the continental shelf and part is spent within estuaries. Adults spawn near the mouth of the Mississippi River, and larvae aggregate within the river plume front. Larval Gulf menhaden transit the continental shelf and ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…Govoni (1997) found that annual Mississippi River discharge was negatively associated with numbers of half-year recruits, and suggested that higher discharges result in an expansive plume, which may propel larvae further offshore and delay the shoreward transport of larvae, hence increasing their vulnerability to predation. Historically, mean monthly discharges of the Mississippi and Atchafalaya Rivers from November through March accounted for nearly 30% of Gulf menhaden recruitment variability in regression analyses (Guillory et al 1983; Vaughan et al 2011). Hence, the oceanographic conditions during winter and spring 2010 should have lowered recruitment of the 2010 Gulf menhaden year class, partially or even entirely offsetting the effects of favorable phytoplankton abundance.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Govoni (1997) found that annual Mississippi River discharge was negatively associated with numbers of half-year recruits, and suggested that higher discharges result in an expansive plume, which may propel larvae further offshore and delay the shoreward transport of larvae, hence increasing their vulnerability to predation. Historically, mean monthly discharges of the Mississippi and Atchafalaya Rivers from November through March accounted for nearly 30% of Gulf menhaden recruitment variability in regression analyses (Guillory et al 1983; Vaughan et al 2011). Hence, the oceanographic conditions during winter and spring 2010 should have lowered recruitment of the 2010 Gulf menhaden year class, partially or even entirely offsetting the effects of favorable phytoplankton abundance.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In the Gulf of Mexico, both a juvenile and adult index of abundance were excluded as predictors due to the limited number of years available. We derived a time series of river discharge ( River Discharge ) for the Gulf of Mexico using annual discharge rates based on the Mississippi and Atchafalaya River flows during the winter months as described in Govoni () and Vaughan et al (). Daily discharge was obtained from the Tarbert Landing gauge located at river mile 306.3 and the Simmesport gauge at river mile 4.9.…”
Section: Methodsmentioning
confidence: 99%
“…Further complicating any understanding of the primary drivers of fish growth is that environmental conditions may operate and interact at different temporal and spatial scales. As an example of the difficulty disentangling factors, in the northern Gulf of Mexico the timing and magnitude of Mississippi River flow affects Gulf Menhaden Brevoortia patronus recruitment, resulting in potential annual variation that could be caused by a changing climate, short‐term variations in river flow, timing of spring thaws, broadscale environmental factors, and landings (Govoni, ; Sanchez‐Rubio & Perry, ; Vaughan, Govoni, & Shertzer, ). All of these factors could also affect growth, and the relative contribution of any one factor may be difficult to quantify.…”
Section: Introductionmentioning
confidence: 99%
“…The results for Gulf menhaden agree with previous analysis showing that environmental drivers are important for understanding recruitment variability. Previous studies have focused on the effect of Mississippi and Atchafalaya river outflow (Govoni, ; Vaughan et al., ) on recruitment. These analyses, however, were based on stock assessments including adult landings data with assumptions such as the natural mortality of menhaden being constant across all years (i.e., independent of ecosystem processes).…”
Section: Discussionmentioning
confidence: 99%
“…For menhaden, there are particular problems stemming from the fact that observational programmes responsible for measuring menhaden juveniles are largely designed around other species (e.g., striped bass). Strong dependence on stochastic environmental drivers is also a common explanation, with studies across both species identifying a wide array of processes that—at least at one time or another—affect recruitment, including longshore wind patterns (Quinlan, Blanton, Miller, & Werner, ), winter storms (Checkley, Raman, Maillet, & Mason, ) and river flow (Govoni, ; Sanchez‐Rubio & Perry, ; Vaughan, Govoni, & Shertzer, ). However, attempts to incorporate environmental information into recruitment forecasts via the traditional “environmental Ricker” (Nelson, Ingham, & Schaaf, ) have not met with much success (Myers, ).…”
Section: Introductionmentioning
confidence: 99%